2021
DOI: 10.1101/2021.10.30.466574
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An arachnid’s guide to be an ant: morphological and behavioural mimicry in ant-mimicking spiders

Abstract: Batesian mimicry imposes several challenges to mimics and evokes adaptations in multiple sensory modalities. Myrmecomorphy, morphological and behavioral resemblance to ants, is seen in over 2000 arthropod species. Ant-like resemblance is observed in at least 13 spider families despite spiders having a distinct body plan compared to ants. Quantifying the extent to which spiders’ shape, size, and behavior resemble model ants will allow us to comprehend the evolutionary pressures that have facilitated myrmecomorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Ant mimicking or myrmecomorph spiders have received considerable attention in studies of evolution through natural selection because they include examples with remarkable morphological adaptations (reviewed by Cushing, 1997; Mclver & Stonedahl, 1993) and are easy to manipulate in laboratory experiments (e.g., Zeng et al., 2023). Experiments have demonstrated that jumping spiders, mantises and mud‐dauber wasps avoid ant‐resembling spiders while readily preying on non‐mimicking spiders (see Subramaniam et al., 2021 for references). However, considering that the largest part of the diversity of ant resembling spiders is found in tropical rainforests, which mostly lack research facilities to perform laboratory trails, several studies support ant mimicry with the identification of species‐specific morphological resemblance in members of sympatric ant and spider communities (e.g., Hashimoto et al., 2016; Perger et al., 2021; Perger & Rubio, 2020a; Reiskind, 1977).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ant mimicking or myrmecomorph spiders have received considerable attention in studies of evolution through natural selection because they include examples with remarkable morphological adaptations (reviewed by Cushing, 1997; Mclver & Stonedahl, 1993) and are easy to manipulate in laboratory experiments (e.g., Zeng et al., 2023). Experiments have demonstrated that jumping spiders, mantises and mud‐dauber wasps avoid ant‐resembling spiders while readily preying on non‐mimicking spiders (see Subramaniam et al., 2021 for references). However, considering that the largest part of the diversity of ant resembling spiders is found in tropical rainforests, which mostly lack research facilities to perform laboratory trails, several studies support ant mimicry with the identification of species‐specific morphological resemblance in members of sympatric ant and spider communities (e.g., Hashimoto et al., 2016; Perger et al., 2021; Perger & Rubio, 2020a; Reiskind, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…These behaviours are assumed to have evolved before morphological mimicry (reviewed by Cushing, 1997) and may be considered adaptations to general ant resemblance. In contrast, species‐specific mimetic behaviour (behaviour that is only observed in specific ants and imitated by their mimics) has not been observed in most studies of behavioural ant mimicry (see Ceccarelli, 2008; McLean & Herberstein, 2021; Nelson & Card, 2016; Oliveira, 1988; Shamble et al., 2017; Subramaniam et al., 2021; Zeng et al., 2023). The mimetic behaviour most likely to be described as species‐specific was the similar speed of three inaccurate spider mimics and their ant models (Pekár & Jarab, 2011).…”
Section: Introductionmentioning
confidence: 99%